Suffer the little children - Eichler-Levine, Jodi (New York University Press, 2016)
Classic and contemporary Jewish and African American children's literature is examined through close readings of selected titles published since 1945. Jodi Eichler-Levine analyses what is at stake in portraying religious history for young people, particularly when the histories in question are traumatic ones. In the wake of the Holocaust and lynchings, of the Middle Passage and flight from Eastern Europe's pogroms, children's literature provides diverse and complicated responses to the challenge of representing difficult collective pasts.
10.18574/nyu/9780814722992.001.0001
Keywords: Juden; Schwarze; Kinderliteratur; Religion; Ethnische Gruppe; Vergangenheit; Leid; Trauma; Children's literature; American; Children's literature; Jewish; American literature; History in literature; Suffering in literature; Jews in literature; African Americans in literature